Identification of specific neutralizing antibodies for highly pathogenic avian influenza H5 2.3.4.4b clades to facilitate vaccine design and therapeutics - Bao Tuan Duong; Seon Ju Yeo; Hyun Park (Emerging Microbes and Infections, 2024)
The highly pathogenic avian influenza H5 2.3.4.4 and 2.3.2.1c subclades have distinct antigenic properties and are responsible for the majority of human infections. Therefore, it is essential to understand the processes by which antibodies inhibit these subclade viruses to develop effective therapies and vaccines to prevent their escape from neutralizing antibodies. Herein, we report the epitopes of two specific monoclonal antibodies (mAbs) targeting haemagglutinin (HA) of the H5 2.3.4.4b subclade and their neutralizing abilities. The results indicated that the two mAbs provided specific protection against the H5 2.3.4.4b clade viral challenge in MDCK cells and mouse models. Through epitope identification and docking studies, we showed that these novel sites (which are located near the 130-loop (S136, T143) and 190-helix (N199, N205) of HA receptor-binding sites that contribute to the binding affinity of neutralizing mAbs and six residues of the complementarity-determining regions) can be targeted to generate antibodies with enhanced cross-neutralization. This can also help in understanding escape mutations that differ among the H5 2.3.4.4b, h, and 2.3.2.1c subclades. These results provide specific information to facilitate future vaccine design and therapeutics for both subclade viruses, which are dominant and pose a serious threat to humans.